Habitus nir-kekerasan: Sebuah upaya mendialogkan habitus Yesus dan pemikiran Pierre Bourdieu tentang pencegahan kekerasan simbolik - Novy Amelia Elisabeth Sine (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2022)
This paper aims to analyze the meaning and significance of the habitus of Jesus and the habitus proposed by Pierre Bourdieu as an approach to overcoming the occurrence of symbolic violence. Symbolic violence is one form of violence that must be watched out for. Schools are one of the places where symbolic violence takes place. This paper uses a qualitative method by conducting a literature study on the meaning of Jesus??